2024
DOI: 10.1161/strokeaha.123.045495
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Alteplase Versus Best Medical Therapy for Patients With Minor Stroke: A Systematic Review and Meta-Analysis

Yang Zhang,
Tian Lv,
Thanh N. Nguyen
et al.

Abstract: Background: The efficacy of thrombolysis (IVT) in minor stroke (National Institutes of Health Stroke Scale score, 0–5) remains inconclusive. The aim of this study is to compare the effectiveness and safety of IVT with best medical therapy (BMT) by means of a systematic review and meta-analysis of randomized controlled trials and observational studies. Methods: We searched the PubMed, Embase, Cochrane Library, and Web of Science databases to obtain artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In the current issue of Stroke, Zhang et al 6 report a thorough meta-analysis of existing studies assessing the value of intravenous thrombolysis for patients who present within the therapeutic window for acute stroke treatment, but who have only minor deficits that would not impact their quality of life. The meta-analysis, which included 20 studies and nearly ≈14 000 patients, confirms what individual studies had previously suggested-patients with small strokes based on the National Institutes of Health Stroke Scale (NIHSS) and in whom deficits are not disabling do not benefit from treatment with intravenous alteplase.…”
Section: See Related Article P 883mentioning
confidence: 99%
“…In the current issue of Stroke, Zhang et al 6 report a thorough meta-analysis of existing studies assessing the value of intravenous thrombolysis for patients who present within the therapeutic window for acute stroke treatment, but who have only minor deficits that would not impact their quality of life. The meta-analysis, which included 20 studies and nearly ≈14 000 patients, confirms what individual studies had previously suggested-patients with small strokes based on the National Institutes of Health Stroke Scale (NIHSS) and in whom deficits are not disabling do not benefit from treatment with intravenous alteplase.…”
Section: See Related Article P 883mentioning
confidence: 99%